Test-Taking Strategies : English Language Art New York Grade 7 - Robin, Janna; Ordover Andrew; Bitz Michael (Kaplan, Inc, 2015)
Provides test-taking strategies, a subject review, coverage of the essays, vocabulary words, and two full-length practice tests with explanations.
At head of title: The Princeton Review.
Keywords: English language -- Composition and exercises -- Examinations -- Study guides; English language -- Examinations -- Study guides; English language -- Composition and exercises -- Examinations, questions, etc; English language -- Examinations, questions, etc; Advanced placement programs (Education) -- Examinations -- Study guides; College entrance achievement tests -- Study guides; Universities and colleges -- Entrance examinations -- Study guides